Why Ride-Hailing Adoption in Developing Regions in Indonesia often fail? : A Case of Maxim Adoption in West Papua Province using Diffusion of Innovation Approach and Theory of Planned Behaviour - Sembor, Ais Fernandes; Inan, Dedi I; Juita, Ratna; Indra, Muhamad (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Ride-hailing services offer various benefits. However, in developing regions it often faces various challenges that hinder its success. This research is important to understand the factors that lead to failed adoption of ride-hailing services, particularly in developing regions in Indonesia. While there are many studies on technology adoption of self-service technology, there is still a gap in the literature that addresses it an a specific context. Using Maxim's adoption in West Papua Province as a case study, this research aims to determine what causes ride-hailing service adoption failure. This research uses a quantitative approach method using the Diffusion of Innovation Approach by analyzing 167 valid respondent data. The results of this study show that relative advantage is the most significant factor driving adoption, followed by perceived financial cost, while resistance to change is the main inhibiting factor in technology adoption, followed by Perceived ubiquity or ease of access to ride-hailing services. This research provides insights for ride-hailing service developers in designing more effective strategies to increase the adoption of new technologies in developing regions.